A Spark in the Dark: Uncovering Natural Activity Patterns of Mormyrid Weakly Electric Fish - Mucha, Stefan; Oehlert, Franziska; Chapman, Lauren J.; Krahe, Rüdiger (Frontiers in Ecology and Evolution, 2022)
To understand animal ecology, observation of wildlife in the natural habitat is essential, but particularly challenging in the underwater realm. Weakly electric fishes provide an excellent opportunity to overcome some of these challenges because they generate electric organ discharges (EODs) to sense their environment and to communicate, which can be detected non-invasively. We tracked the EOD and swimming activity of two species of mormyrid weakly electric fishes (Marcusenius victoriae and Petrocephalus degeni) over diel cycles in the laboratory, and we recorded EODs and environmental dissolved oxygen (DO) concentration and temperature over several months in a naturally hypoxic habitat in Uganda. Under laboratory conditions, both species showed increases of activity and exploration behavior that were closely synchronized to the onset of the dark phase. In the wild, fish preferred structurally complex habitats during the day, but dispersed towards open areas at night, presumably to forage and interact. Nocturnal increase of movement range coincided with diel declines in DO concentration to extremely low levels. The fact that fish showed pronounced nocturnal activity patterns in the laboratory and in the open areas of their habitat, but not under floating vegetation, indicates that light intensity exerts a direct effect on their activity. We hypothesize that being dark-active and tolerant to hypoxia increases the resistance of these fish against predators. This study establishes a new technology to record EODs in the field and provides a window into the largely unknown behavior of mormyrids in their natural habitat.